Visual Representation Determines Search Difficulty: Explaining Visual Search Asymmetries - Bruce, Neil; Tsotsos, John (Frontiers in Computational Neuroscience, 2011)
In visual search experiments there exist a variety of experimental paradigms in which a symmetric set of experimental conditions yields asymmetric corresponding task performance. There are a variety of examples of this that currently lack a satisfactory explanation. In this paper, we demonstrate that distinct classes of asymmetries may be explained by virtue of a few simple conditions that are consistent with current thinking surrounding computational modeling of visual search and coding in the primate brain. This includes a detailed look at the role that stimulus familiarity plays in the determination of search performance. Overall, we demonstrate that all of these asymmetries have a common origin, namely, they are a consequence of the encoding that appears in the visual cortex. The analysis associated with these cases yields insight into the problem of visual search in general and predictions of novel search asymmetries.